SALIVARY SPECIFIC IgE TO D1 AND G6 IN PATIENTS WITH RHINITIS WITH OR WITHOUT S. AUREUS COLONIZATION - Diana Hristova; Antoaneta Decheva; Deyan Donchev; Damyan Vangelov; Vancho Donev; Georgi Nikolov; Maria Nikolova (Problems of Infectious and Parasitic Diseases)
Globally, allergic rhinitis impacts roughly 25% of children and 40% of adults. Immunoglobulin E (IgE) plays a crucial part in allergic inflammation, with two sources: spontaneously produced IgE, and IgE stemming from reactions to environmental allergens. The damaging effects of S. aureus, as well as Staphylococcal enterotoxins (Ses), have been proven in numerous airway illnesses. As superantigens, Ses generate intense Th2 inflammation, with 70-80% of IgE being locally synthesized. Our study aimed to determine if any correlation existed between local and systemic specific IgE responses in rhinitis patients – both treated and untreated. Furthermore, we sought to pinpoint significant disparities in serum allergy-specific IgE levels between S. aureus positive and negative patients.